Intentional Subtotal Resection of Vestibular Schwannoma: A Reexamination - Strickland, Ben A.; Ravina, Kristine; Rennert, Robert C.; Jackanich, Anna; Aaron, Ksenia; Bakhsheshian, Joshua; Russin, Jonathan J.; Friedman, Rick A.; Giannotta, Steven L. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Treatment of vestibular schwannomas (VS) remains controversial. Historical surgical series prioritized gross total resections (GTR); however, near total resections (NTR) and intentional subtotal resections (STR) aiming at improving cranial nerve outcomes are becoming more popular.Objective The main purpose of this article is to assess the tumor control and facial nerve outcomes in VS patients treated with STR or NTR.Methods VS patients undergoing STR or NTR at our institution between 1984 and 2016 were retrospectively reviewed. Patient demographics, extent of tumor resection, facial nerve injury, tumor recurrence, and need for Gamma Knife radiosurgery were analyzed. Facial nerve outcomes were quantified using House–Brackmann (HB) scores. Tumor regrowth was defined by the San Francisco criteria.Results Four-hundred fifty-seven VS resections were performed in a 32-year period. Sixty cases met inclusion criteria. The mean (range) follow-up duration was 30.9 (12–103) months. The STR cohort (n = 33) demonstrated regrowth in 12 patients (36.3%) at an average of 23.6 months. The NTR cohort (n = 27) did not experience tumor recurrence. Risk of tumor recurrence was positively correlated with preoperative tumor size (p = 0.002), size of residual tumor (p < 0.001), and STR (p < 0.001). Facial nerve outcomes of HB1–2 were observed in the majority of patients in both cohorts (74.1% NTR, 56% STR), though NTR was associated with a higher likelihood of facial nerve recovery (p = 0.003).Conclusion GTR remains the gold standard as long as facial nerve outcomes remain acceptable. NTR achieved superior tumor control and higher likelihood of facial nerve recovery compared with STR.
Keywords: vestibular schwannoma; subtotal resection; near total resection; skull base surgery